Prevalence of Traditional and Complementary Alternative Medicine’s Use among Cancer Patients in South Peninsular Malaysia - Razali, Nurul Huda; Ali, Aisyah; Hua Gan, Siew; Sen Lim, Chun (Asian Pacific Journal of Cancer Biology, 2020)
Objective: This study sought to describe the use of traditional and complementary alternative medicine’s (CAM) in a cohort of cancer patients in Johor, a state in Southern Peninsular Malaysia. Methodology: This is a four-month cross sectional study, targeted, on cancer outpatient clinics in three hospitals. Ethical approval and signed written informed consents were obtained from the patients, prior to the study. A standardised, interviewer-administered questionnaire was used to obtain the socio-demographic characteristics, clinical characteristics and questions on CAM’s use. Results: The response rate was 95.4%. The majority of the participants was females (79.9%) and was from the Malay ethnic group (79.2%) with most having only a secondary education (41.8%). The mean age was 57.7 ± 12.47 years with the majority having breast cancer (51.1%). There were no significant association between the socio demographic variables with CAM’s use with the exception of hospital, participants’ religion and ethnicity (p-value < 0.05). Many patients preferred biologically-based therapies (87.8%) such as herbs and dietary supplements with a large proportion having reported to have utilised CAM after having completed the conventional treatment (40.0%). The majority (60.1%) of the patients were satisfied with CAM treatment while only 17.40% showed dissatisfaction. Most cancer patients chose CAM due to their perceived fewer side effects (31.1%), to increase quality of life (26.7%) and as a curative intent (20.7%). Conclusion: There is a high prevalence of CAM’s use among cancer patients in Southern State in Malaysia.